ALASAN AMERIKA SERIKAT DALAM MENEMPATKAN PANGKALAN MILITER DI DARWIN AUSTRALIA TAHUN 2011 - Suci Lestari; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aimed to analyze the reasons the United States in placing military base in Darwin, Australia in 2011. The placement of the United States military base in Darwin is one realization of the ANZUS as a military Treaty Organization the United States and Australia. In the placement of military bases starting with the delivery of 200 troops to Darwin and in 2014 increased to 1100 troops. This research will discuss why the United States put a military base in Darwin, Australia. This research applying qualitative methods and library research. The author use security theory from Bary Buzan with Balance of Power concept, with perspektif realism and use the level of the nation-state analysis. The sources of this research are from of books, journals,documents, articles and internet. This study find that the United States put a military base in Darwin because the United States wants to prevent the influence of China in the Asia Pacific region. China made a string of pearls strategy which is the main import and export shipments of oil china. china influence in the Asia Pacific region can also be seen from china perform claiming against the south china sea area. China's increasingly assertive and often aggression in this disputed region. Placement of the US military base in Darwin is an act of the United States to prevent the influence of China in the Asia Pacific regionKeywords: military base, asia pacific, threat, stability of asia pacific